2012
DOI: 10.1016/j.bone.2012.02.639
|View full text |Cite
|
Sign up to set email alerts
|

Effect of co-morbidities on fracture risk: Findings from the Global Longitudinal Study of Osteoporosis in Women (GLOW)

Abstract: Introduction Greater awareness of the relationship between co-morbidities and fracture risk may improve fracture-prediction algorithms such as FRAX. Materials and methods We used a large, multinational cohort study (GLOW) to investigate the effect of co-morbidities on fracture risk. Women completed a baseline questionnaire detailing past medical history, including co-morbidity history and fracture. They were re-contacted annually to determine incident clinical fractures. A co-morbidity index, defined as numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
89
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(99 citation statements)
references
References 42 publications
6
89
0
4
Order By: Relevance
“…We note, however, that incidence rates of vertebral and hip fracture observed among patients unexposed or exposed to low levels of steroids in our study are comparable to those reported for post-menopausal women aged 50-70 years in the general population [31,32]. In contrast to previous studies of glucocorticoid users with diverse disease [15,[33][34][35][36][37], we may have better isolated the impact of glucocorticoid use on fracture risk by focusing on incident RA patients and, thus, decreasing the potential for disease-related confounding. This approach also reduced the heterogeneity in patterns of steroid use, which varies by disease.…”
Section: Discussionsupporting
confidence: 54%
“…We note, however, that incidence rates of vertebral and hip fracture observed among patients unexposed or exposed to low levels of steroids in our study are comparable to those reported for post-menopausal women aged 50-70 years in the general population [31,32]. In contrast to previous studies of glucocorticoid users with diverse disease [15,[33][34][35][36][37], we may have better isolated the impact of glucocorticoid use on fracture risk by focusing on incident RA patients and, thus, decreasing the potential for disease-related confounding. This approach also reduced the heterogeneity in patterns of steroid use, which varies by disease.…”
Section: Discussionsupporting
confidence: 54%
“…Comorbidities to be mentioned include rheumatoid arthritis and connective tissue diseases, diabetes, chronic obstructive pulmonary disease, chronic inflammatory bowel diseases, AIDS, Parkinson's disease, multiple sclerosis, conditions associated with severe motor disability. Of note, individuals with type 1 or type 2 diabetes tend to fracture at a higher BMD as compared to non-diabetic subjects, therefore the risk of fracture is partially independent of BMD in this population (7)(8)(9)(10)(11)(12)(13)(14)(15).…”
Section: • Female Gendermentioning
confidence: 96%
“…45 This study found that the predictive power of the FRAX algorithm was improved when specific co-morbidities, including MS, were incorporated.…”
Section: Fracture Risk In Msmentioning
confidence: 84%